Culture in a liquid modern world - Bauman, Zygmunt, 1925-; Bauman, Lydia (Cambridge, UK ;Malden, MA : Polity ; [Warsaw] : In association with the National Audiovisual Institute, 2011)
"In its original formulation, 'culture' was intended to be an agent for change, a mission undertaken with the aim of educating 'the people' by bringing the best of human thought and creativity to them. But in our contemporary liquid-modern world, culture
"This book was commissioned by the National Audiovisual Institute for the European Culture Congress, 8-11 September, Wroclaw, Poland."--T.p. verso. Includes bibliographical references. Some notes on the historical peregrinations of the concept of 'culture
Keywords: Culture -- Pilosophy; Kültür -- Felsefe